Unleashing the immune modulatory potential of Leishmania amazonensis-derived extracellular vesicles in American cutaneous leishmaniasis - de Freitas, Bruna Eugênia; Rodrigues, Armanda; Palma-Marques, Joana; Weber, Juliana Inês; Valério-Bolas, Ana; Soares, Rodrigo Pedro; Torrecilhas, Ana Claudia; Ferla, Micheli; Muhammad Abdel Baqui, Munira; Gonzales Cordova, Raul Alexander; Alexandre-Pires, Graça; Pereira da Fonseca, Isabel; et al. (Frontiers in Molecular Biosciences, 2025)
IntroductionAmerican cutaneous leishmaniasis (ACL) constitutes a neglected skin disease that causes severe disability and significant social stigma for millions of people each year. This parasitic infection is caused by several species of the protozoan Leishmania, including Leishmania amazonensis. There is therefore an urgent need to develop effective new tools to control ACL, primarily due to the limitations of current prophylactic and therapeutic strategies, which are exacerbated by the growing burden of the disease and its social impact. In recent years, scientific research has focused on extracellular vesicles (EVs), which are lipid-enclosed rounded nanostructures that carry macromolecules to recipient cells and are part of eukaryotic biology. The role of Leishmania-derived EVs in host pathogenesis has attracted considerable attention among researchers, with studies suggesting that EVs may play a key role in modulating the host immune response. Therefore, this study examined the immunogenicity and protein cargo of EVs shed by L. amazonensis, exploring their effect on immune activation in the murine macrophages (MΦs) lineage.MethodsNanoparticle tracking analysis, microscopy, proteomic methodologies, colorimetric assays, serological immune methods, PCR, and multiparametric flow cytometry were employed.ResultsEVs derived from L. amazonensis cultured promastigotes contain key components, such as the 63 kDa surface glycoprotein, intracellular heat shock protein 70, and α-type proteasome subunit, which may be involved in parasite survival. Moreover, EVs are recognized by mouse- and human-specific antibodies, indicating that they have the potential to elicit humoral immune responses and can be inactivated by host-specific antibodies. Depending on the concentration, EVs can drive MΦs to express MHC molecules that are essential for antigen presentation to T lymphocytes, thereby being able to promote a cellular immune response. EVs favor IL-1β+MΦs contraction, and low nitric oxide production, and activate the arginase pathway to produce urea along with the generation of proinflammatory cytokines. This MΦs modulation may support parasite control through the specific activation of T cells while preserving skin homeostasis, thereby reducing the pathology associated with L. amazonensis infection, which causes ACL and leads to the development of chronic disease.DiscussionThus, this study’s findings suggest that although L. amazonensis-derived EVs can trigger MΦs activation, favoring a pro-inflammatory immune response, they also have the potential to ensure parasite survival while limiting host pathogenesis. This can be advantageous for parasite transmission and essential for completing the parasite life cycle.